Who’s afraid of Patterns?: The Particular versus the Universal and the Meaning of Humanities 3.0 - Bod, Rens (BMGN - Low Countries Historical Review, 2013)
The advent of Digital Humanities has enabled scholars to identify previously unknown patterns in the arts and letters; but the notion of pattern has also been subject to debate. In my response to the authors of this Forum, I argue that ‘pattern’ should not be confused with universal pattern. The term pattern itself is neutral with respect to being either particular or universal. Yet the testing and discovery of patterns – be they local or global – is greatly aided by digital tools. While such tools have been beneficial for the humanities, numerous scholars lack a sufficient grasp of the underlying assumptions and methods of these tools. I argue that in order to criticise and interpret the results of digital humanities properly, scholars must acquire a good working knowledge of the underlying tools and methods. Only then can digital humanities be fully integrated (humanities 3.0) with time-honoured (humanities 1.0) tools of hermeneutics and criticism. This article is part of the forum ’The End of the Humanities 1.0’.